Cation vacancy repair for the enhancement of orange-yellow luminescence in Sr9Mg1.5−xKx(PO4)7:Eu2+ phosphors. Issue 40 (24th September 2018) - Yu, Liping; Yan, Huifang; Fan, Yanting; Zhang, Jinhui; Ma, Zhongyun; Zhou, Wenli; Chen, Yan; Pan, Fengjuan; Lian, Shixun
Abstract : A cation vacancy repair strategy successfully improves the photoluminescence of the Sr9 Mg1.5 (PO4 )7 :Eu 2+ phosphor by K substituting Mg and Mg-vacancies. Abstract : Many approaches have contributed to improving the luminescence properties of phosphors, including surface coating, direct reduction and charge compensation, which are involved in reducing the inner or surface defects of luminescent particles. In this study, we propose a cation vacancy repair strategy to successfully improve the orange-yellow luminescence properties of the Sr9 Mg1.5 (PO4 )7 :Eu 2+ phosphor. The main idea of the strategy is that introducing K + repairs the vacancy at the Mg(1) site according to the formula . The preferred substitution of the large Mg(1) site by K + is supported by theoretical calculations. As a result, the luminescence of the repaired phosphate phosphor was enhanced by 2.5 times, and the internal and external quantum efficiency significantly increased by 50.5% and 55.4%, respectively. Additionally, the thermal stability was also a little improved. The enhancement mechanisms for luminescence are discussed in detail based on investigations of the microstructure, luminescence spectra, decay curves and concentration using various analysis techniques. We find that low luminescence efficiency is due to the existence of vacancy defects in the phosphor. Through using the repaired Sr9 MgK(PO4 )7 :Eu 2+ phosphor, a white LED package demonstrated a low correlated color temperature (∼2900 K), high color rendering index (∼90) and R9 > 91. We expect that the strategy proposed herein would improve luminescence for other phosphors with vacancy defects.